Implementasi Shalat Zuhur Berjamaah dalam Membentuk Karakter Disiplin Peserta Didik Kelas Tinggi di SD Negeri 09 Ulakan Tapakis - Andriani, Widya; Saputra, Edi (Lembaga Yasin AlSys, 2024)
Congregational prayer is a prayer performed by two or more people, one of whom is the imam and the other is the congregation with the terms and conditions of congregational prayer. Of the high class students, the majority are still unable to follow the imam's movements in carrying out congregational prayers, students are not yet orderly and regular in carrying out congregational prayers. This research aims to determine the implementation of congregational Zuhr prayers in shaping the disciplined character of high class students at SD Negeri 09 Ulakan Tapakis as well as the supporting and inhibiting factors. This research includes qualitative research with a descriptive approach. The data analysis techniques used are data collection, data reduction, data presentation, and data verification. The results of the research show that the implementation of midday prayers in congregation in forming the disciplined character of high class students at SD Negeri 09 Ulakan Tapakis includes three activities, namely carrying out ablutions guided by PAI teachers, carrying out midday prayers in congregation at school carried out by students, after carrying out midday prayers in congregation with teachers. provide advice and direction regarding prayer movements to students. From the implementation of the congregational Zuhr prayer, it is carried out with the students' self-awareness so that it can form the disciplined character of the students. Supporting factors for the congregational Zuhr prayer include students being accustomed to carrying out religious activities at school, the school providing prayer mats and mukenas, all teachers and students taking care of it. cleanliness of facilities for carrying out congregational Zuhr prayers. The inhibiting factors are inadequate school facilities, inadequate teacher management and supervision of students.